An approach to plan and evaluate the location of radiotherapy services and its application in the New South Wales, Australia. Issue 2 (November 2015) - Shukla, Nagesh; Wickramasuriya, Rohan; Miller, Andrew; Perez, Pascal
Highlights Proposes a methodology for location planning of radiotherapy treatment services. The methodology is based on cancer incidence and road network-based accessibility measures. Applied to the current radiotherapy treatment centres in New South Wales state of Australia. Current and future regional radiotherapy demand are estimated.